Efficiency Wages and Industry Wage Differentials: A Comparison Across Methods of Pay - Chen, Paul; Edin, Per-Anders (The Review of Economics and Statistics, 2002)
Efficiency wage considerations should be less important for piece-rate pay than for time wages. Therefore, if industry wage differentials reflect efficiency wage factors, then these pay differences should be less sizable and have less explanatory power for piecework than for timework. We test this proposition using wage data for male production workers employed in the Swedish metalworking industries in 1985. The data are partitioned into two groups of workers. In our preferred sub-sample of workers who received pay under both piece rates and time wages, our results are uniformly consistent with efficiency wage implications for industry wage differentials. For the subsample of workers who received pay under either piece rates or time wages, industry wage differentials are of equal importance under either pay scheme. These latter results, however, may also be influenced by unaccounted for sorting of workers and employers across methods of pay. Overall, our examination of industry wage differentials across methods of pay provides mixed support for efficiency wage theory.